French art song history of a new music, 1870-1914 - Kilpatrick, Emily 1983- (Eastman studies in music, 2024)
A ground-breaking study of the musical and literary priorities, professional practices and creative interactions that shaped one of the most adventurous artforms of the Belle Époque